Pengaruh Mediasi Kepuasan Konsumen pada Hubungan antara Persepsi Kualitas Layanan, Persepsi Keadilan Harga, dan Loyalitas di Excelso Surabaya - Verrelie, Ferrel Christian; Agustiono, Agustiono (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2024)
This article aims to provide an in-depth analysis of the factors influencing customer loyalty at Excelso. Specifically, the study examines the impact of perceived service quality and price fairness on customer loyalty, with consumer satisfaction as a potential mediating variable. A quantitative research approach is employed, utilizing Smart PLS as an analytical tool to comprehensively calculate and process statistical data. Due to the inability to determine the exact number of Excelso customers in Surabaya, the researcher applies a non-probability sampling method, namely purposive sampling, using the Lemeshow formula to determine an optimal sample size of 96 respondents. Data were collected through an online questionnaire utilizing a 6-point Likert scale to minimize neutral response bias. The findings reveal a significant relationship between perceived service quality and customer loyalty, as well as between price fairness and customer loyalty. Additionally, consumer satisfaction was found to play an important mediating role in strengthening the relationship between service quality and price fairness on loyalty, thus enhancing customer commitment to the products and services offered.